Exploring Driver’s Response to Variable Road Pricing (VRP) Scheme: An Insight into Policy Implementation in Indonesia - Yos Sunitiyoso; Fikri Hadiansyah; Shimaditya Nuraeni; Mila Jamila Khatun Badriyah (Jurnal Manajemen dan Bisnis Indonesia, 2018)
In the last few decades, road pricing scheme have been known to hold a central role in actualizing sustainable and integrated transport systems. Road pricing has been implemented in various forms and price structures in many cities in the world. Although the road pricing and price structures were generally designed based on the rational actor approach, some studies provided evidences that, in reality, drivers have bounded rationality. It can be argued that limited cognitive ability of drivers gave significant effect towards their decision. In developing countries like Indonesia, road pricing seems to be an alternative solution for traffic congestion problems. This research aims to explore the cognitive responses of drivers, particularly on their ways of making decision and learning, to complexity and variability of road pricing, and also to give valuable contribution to the government on making policy towards traffic issues. The initial results indicate that policy makers in Indonesia need to consider how drivers behave in response to road pricing scheme before implementing any road pricing policy. Moreover, multiple factors from the point of view of drivers (travel time, safety, comfort, etc.) should be taken into consideration as integral parts of the road pricing scheme design. Keywords: driver behaviour, experiment, road pricing, road pricing policy